Mild acetabular dysplasia and risk of osteoarthritis of the hip: a case–control study. Issue 10 (14th May 2010) - McWilliams, Daniel F; Doherty, Sally A; Jenkins, Wendy D; Maciewicz, Rose A; Muir, Kenneth R; Zhang, Weiya; Doherty, Michael
Abstract : Objective: To determine whether mild variation in acetabular depth (AD) and shape is a risk factor for osteoarthritis (OA) of the hip. Methods: The unaffected contralateral hip of patients with unilateral hip OA was compared with hips of asymptomatic controls without hip OA, derived from the Nottingham Genetics Osteoarthritis and Lifestyle case–control study. Standardised anteroposterior x-rays of the pelvis were used to measure centre edge (CE) angle and AD. Cut-off points for narrow CE angle and shallow AD were calculated from the control group (mean −1.96×SD). The relative risk of hip OA associated with each feature was estimated using OR and 95% CI and adjusted risks were calculated by logistic regression. Results: In controls, both the CE angle and the AD were lower in the left hip than in the right hip. The CE angle related to age in both hips, and AD of the right hip was lower in men than in women. The contralateral unaffected hip in patients with unilateral hip OA had a decreased CE angle and AD compared with controls, irrespective of side. The lowest tertile of the CE angle in contralateral hips was associated with an eightfold risk of OA (aOR 8.06, 95% CI 4.87 to 13.35) and the lowest tertile of AD was associated with a 2.5-fold risk of OA (aOR 2.53, 95% CI 1.28 to 5.00). Significant increases in the risk of OA were also found as the CE angle and AD decreased. Conclusion: Constitutional mild acetabular dysplasia appears to increase the risk of hip OA.